We look past that’: Linguistic repertoires and ideologies of Business Studies teachers at a South African High School - Oostendorp, Marcelyn; Williams van Zyl, Sasha (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
This paper reports on the linguistic repertoires and language ideologies of a small group of Business Studies teachers at a high school in Cape Town, South Africa. Using language portraits and focus group interviews to collect data, we found through a thematic analysis that teachers talked about their own repertoires as performative, playful, and innovative. By contrast, the repertoires of their students are not described in the same manner. Instead, the teachers either erase big parts of their students’ linguistic repertoires or see “accents” and African languages as deficient. African languages are seen as not suitable to use as a language of teaching and learning and is constructed as hampering rather than facilitating educational progress. We use the notion of chronotope to explain how the school as an institution shapes the different narratives evoked around repertoires. Finally, we discuss the implications of our findings for teacher pedagogy.